Wprowadzenie do obrotu jako znamię wybranych typów czynów zabronionych uregulowanych w pozakodeksowym prawie karnym : analiza orzecznictwa - Piątkowska, Katarzyna (Koło Naukowe Doktryn Politycznych i Prawnych, Katedra Doktryn Politycznych i Prawnych, Wydział Prawa, Administracji i Ekonomii Uniwersytet Wrocławski, 2016)
The author of the article conducts a thorough analysis of the concept of “placing on market”, which is a feature of many criminal offences included in different acts. The Polish Supreme Court found, that “placing on market” is defined as first, and only first, transmission of goods marked with a forged trademark to traffic by their producer or importer. Such an interpretation caused huge controversy in doctrine, the effect of which were many judicial glosses written by the opponents and supporters of this opinion. The opponents claimed that “placing on market” includes also the acts of trading goods marked with a forged trademark. The effect of the debate between doctrine’s representatives was the amending of provisions of The Industrial Property Law Act in 2007 and the which took place on the 29th of June 2007 and the Pharmaceutical Law Act in 2014. The author presents different views of doctrine’s representatives on the interpretation of the concept of “placing on market” and, referring to different acts, legal definitions and legal rules, shows her own point of view.
Keywords: wprowadzanie do obrotu; wykładnia językowa; orzecznictwo